A divat szereplői: olasz cégek Magyarországon - Sacchetto, Devi; Somos, Angéla (Szociológiai Szemle, 2024)
The paper presents a research dealing with the experiences o f the investment of Italian textile and garments industry, based on specific chains of a putting-out system, in Hungary. In the fashion branch of the Italian economy the main actors of international expansion are those suppliers and traders who have emerged from the sphere of small entrepreneurs and independent producers, showing an incredible growth in the North Italian areas. This type of the system o f international subcontractors is able to maintain the flexibility of the production processes of manufacturers and it is even able to reduce costs, basing its production on external outwork, including Hungarian partners. The paper presents such actors of the Italian putting-out system like the independent merchant-entrepreneurs, the so-called ’travelling’ technicians who have acquired professional experience in manufacturing firms, and the managers employed here. The paper also describes their tasks in operating the Hungarian companies. The research has repeatedly found that in this low-pay branch Hungarian labour had shown resistance towards the system of division of labour, based on strict specialisation of the Italian companies, which has restricted their autonomy at work and their internal communication in the place of work.